Development of a Phage‐Display Derived Peptide‐Based Colloidal Gold Strip for Rapid Detection of Enterocytozoon hepatopenaei via Spore Wall Protein Interaction - Jia‐rong Xie; Hao Li; Ben Chen; Yan‐chang Fan; Yu‐hao Gong; Liqun Lu (Journal of Fish Diseases, 2025)
Infection by Enterocytozoon hepatopenaei (EHP) leads to stunted or arrested growth in shrimp, causing significant economic losses in shrimp aquaculture. In this study, the spore wall protein EhSW12 was expressed using a prokaryotic expression system. Subsequently, phage display technology was employed to screen for peptides that interact with EhSW12. A rapid detection method was developed that bypasses the laborious procedure of extracting tissue DNA samples. Instead, enzymatic digestion was used to lyse the spore wall protein present in tissue homogenates, thereby enabling direct detection of EhSW12 via antigen colloidal gold rapid test strips and dot blot assays. The colloidal gold test strips, noted for their convenience and rapidity, satisfy the requirements for on‐site testing, while the dot blot method—with its simple operation—is well suited for high‐throughput sample analysis. Both methods were compared with the national standard qPCR assay. Specificity was validated using various shrimp antigens prepared in the laboratory; the results demonstrated that only the EHP antigen yielded a positive reaction, with no cross‐reaction observed with other common shrimp pathogens (e.g., white spot syndrome virus, decapod iridescent virus and highly pathogenic Vibrio ). Sensitivity tests indicated that the minimum detection limits for the test strip and dot blot methods were, respectively, 7 × 10 6 copies and 5.2 × 10 4 copies. In summary, both methods exhibit strong specificity, high sensitivity, rapid detection speed and operational simplicity—characteristics that make them highly suitable for large‐scale on‐site rapid testing.

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.